KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII A SMP NEGERI 10 KUPANG - asbanu, sufince; Margareta, Karus M.; Djokaho, Margareta P.E (Jurnal Lazuardi, 2025)
Sufince Antonia Asbanu. Student ID 2101010088. Supervised by Dra. Karus M. Margareta, M.Pd and Margareta P.E Djokaho, S.Sn.M.Pd. Writing Ability of Descriptive Text of Class VII A Students of SMP Negeri 10 Kupang. The problem raised in this study is How is the Writing Ability of Descriptive Text of Class VII A Students of SMP Negeri 10 Kupang?. The purpose of this study is to describe the Writing Ability of Descriptive Text of Class VII A Students of SMP Negeri 10 Kupang. The theory used is constructivism and writing theory. The method used in this study is descriptive qualitative. The data collection technique used in this study is the test technique. The data analysis technique in this study is reading students' descriptive texts, identifying descriptive texts according to the structure and language rules, analyzing student data by scoring, and concluding the results of the data analysis. The results of the study showed that, class VII A students of SMP Negeri 10 Kupang were able to write descriptive texts well based on the structure and language rules of descriptive texts. Text structure with a percentage of students who completed 78.6% and a percentage of students who did not complete 21.4%. Language rules with a percentage of students who completed 64.9% and a percentage of students who did not complete 35.1%. Based on the research that has been done, it can be concluded that students in class VII A of SMP Negeri 10 Kupang are categorized as capable of writing descriptive texts. This shows that there are students who produce descriptive texts very well and there are also students who do not produce descriptive texts well. This shows the level of ability of students in class VII A of SMP Negeri 10 Kupang in writing descriptive texts in accordance with the structure and language rules of descriptive texts are able to achieve the KKTP score standard of 75.